Whiffs that weave : a visual recipe cookbook that strings together home-cooked recipes of neighbours in a HDB block - Lye, Joanne Shuyi (2017)
Whiffs that Weave is a visual recipe cookbook that aims to string together home-cooked recipes of neighbours from various cultural backgrounds in a particular HDB community in Sengkang. Noticing a decline in neighbourliness through the decades where neighbours have become more insular and less connected to each other, I aspire to re-ignite/revive this traditional Kampung spirit among Singaporeans once more. Hence, through this project, I hoped to highlight the essence of neighbourliness by getting to know my neighbours one dish at a time through their cooking, as well as spawn a shared platform in which neighbours can participate in and contribute their treasured recipes. Through this, opportunities are created for neighbours to learn more about each other through their shared recipes and different cultural backgrounds, altogether enhancing greater inter-neighbour interactions and ultimately fostering a culture of neighbourliness.